Impact of Roots and Rhizomes on Wetland Archaeology: A Review. (2nd October 2015) - Tjelldén, Anna Katarina Ejgreen; kristiansen, Søren Munch; Matthiesen, Henning; Pedersen, Ole
Abstract : The general premise for successful archaeological in situ preservation in wetlands is that raising the water table will 'seal the grave' by preventing oxygen from reaching the deposit. The present review reveals that this may not be the entire picture, as a change in habitat may introduce new plant species that can damage site stratigraphy and artefacts. However, reviews on the types and degree of damage caused by vegetation to archaeological remains preserved in situ in wetlands have hitherto only been sporadically treated in the literature. Thus, this paper provides an overview of the adverse effects that various plants species have on the preservation status of wetland archaeology.Disturbance, due to growth of roots and rhizomes of the surrounding soil is denoted contextual disturbance, whereas deterioration of archaeological remains per se acts by several root-related factors that may be spatially and temporally concomitant. In waterlogged anoxic environments, deterioration is mainly related to (i) preferential growth of roots/rhizomes due to nutrient uptake and lesser soil resistance, (ii) root etching due to organic acid exudates, (iii) microbial growth due to root release of oxygen and labile organic compounds, and/or (iv) precipitation of hydroxides due to root release of oxygen. For example, roots of some wetland plants, such as marsh horsetail ( Equisetum palustre ), have been documented to penetrate archaeological artefacts down to c . 2 m in waterlogged anoxic soils. Here, we demonstrate that cultural heritage site management may unintentionally introduce deep-rooted or exudate aggressive plants by invoking change in hydrological conditions. Moreover, the implementation of biomass energy utilization and agricultural root depth optimization on a worldwide basis stresses the need for more research within root and rhizome impact on archaeological remains in wetlands. In conclusion, the worst-case scenario may be in situ deterioration instead of preservation, and one essential threat to archaeological wetland sites is the impact of wetland vegetation.